Analisis dan Perbaikan Proses Bisnis dengan menggunakan Teknik Esia (Studi Kasus : Departemen Produksi PT XYZ) - Merlien Yuliana Permatasari; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The more the business market continues to increase. Companies need to give products / services better. PT XYZ is a company engaged in the processing of marine products, especially anchovy. Production department is a department that has a great influence on the company. Currently in running its business process, the production department of PT XYZ is experiencing difficulties in managing the stock. The purpose of this research is to doing current business process modeling (as-is) at PT XYZ production department, provide recommendations on proposed business processes (to-be) submitted to PT XYZ production department using ESIA techniques, and produce a comparison of current business processes with proposed business processes at the production department of PT XYZ. Research begins with literature studies and data collection through interviews next is modeling business processes using BPMN, determining business process recommendations, problem identification, value added analysis, design improvements using ESIA techniques and comparison results of process simulations. The results obtained from this research that is obtained eight business process models that can later be evaluated and effectiveness, recommended business process models using ESIA techniques, and comparison results of the current business process simulation and business process recommendations.